2019
DOI: 10.1136/bcr-2019-229327
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous mass concerning for sarcoma: a peculiar presentation of diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) can present in a number of different ways, including as a primary cutaneous lesion or at various other extranodal sites. However, it is rare for a DLBCL to present as a clinically subcutaneous mass without visible skin changes or nodal involvement. A 36-year-old man presented with a 4×4×1 cm subcutaneous mass to his shoulder with normal overlying skin which had been enlarging over 6 months. Physical exam and imaging together made a strong case for sarcoma, and the patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Mamorska-Dyga et al reported a case of right arm violaceous fleshy tumor above the antecubital fossa that was initially thought to be a sarcoma based on physical examination and imaging results but after biopsy was diagnosed to be DLBCL [ 4 ]. Mayo et al reported a case of DLBCL of the subcutaneous tissue of the right shoulder with completely normal skin and absent lymph nodes that underwent complete surgical excision under the impression of sarcoma [ 5 ]. In addition to DLBCLs, other types of lymphoma may also involve the soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Mamorska-Dyga et al reported a case of right arm violaceous fleshy tumor above the antecubital fossa that was initially thought to be a sarcoma based on physical examination and imaging results but after biopsy was diagnosed to be DLBCL [ 4 ]. Mayo et al reported a case of DLBCL of the subcutaneous tissue of the right shoulder with completely normal skin and absent lymph nodes that underwent complete surgical excision under the impression of sarcoma [ 5 ]. In addition to DLBCLs, other types of lymphoma may also involve the soft tissue.…”
Section: Discussionmentioning
confidence: 99%